Adequacy of earnings replacement in workers' compensation programs : a report of the Study Panel on Benefit Adequacy of the Workers' Compensation Steering Committee, National Academy of Social Insurance - Hunt, H. Allan (W.E. Upjohn Institute for Employment Research, 2004)
Annotation In 1998, NASI convened a study panel of its Workers' Compensation Steering Committee (seep. 145 for a list of panel members) to review the earnings replacement benefits under the variousstate and federal workers' compensation programs for workers injured or made ill by their jobs. The Benefit Adequacy Study Panel's task was to examine the extent to which workers'compensation wage replacement benefits paid to injured workers replace their lost wages, and toassess the adequacy of wage replacement.